Learning Loss with Arabic Learner Autonomy in Limited Face-To-Face Policy (PTM) at Jambi Province - Sulhi M. Daud; Abdul Muid; Muhammad Sobri (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
Learner autonomy is the main solution for overcoming learning loss in the limited face-to-face policy (PTM) that was implemented in Indonesia in early 2022. This research is based on the phenomenon of the decreasing quality of learning Arabic due to the pandemic. A qualitative research approach with the type of case studies used in this research is used to reveal the decline in learning and independent learning at tertiary institutions in Jambi Province. A case study approach is used in this study. The main findings and results are described by uncovering a case of learning loss in limited face-to-face policies in Jambi Province. This research addresses two main focuses: First, the phenomenon of learning loss is caused by several factors, such as adaptation to hybrid learning, limited internet access, minimal learning platform services, and technological stuttering. Finally, learner autonomy on limited face-to-face learning (PTM) policies in Jambi implementation of independent learners By the Autonomy Learning Scale (ALS), fulfilling the seven aspects of self-learning implementation with the highest (good enough) score on the three categories of self-awareness indicators (6.5 score), self-effort (6.5 and extensive autonomous activities (6.7 score) achieves a score of 6.7. And the low category on the aspect of self-confidence with a score of 2.5 and motivation, which only gets a score of 0.5.